History and its image in recent Czech prose - Vanicek, Jakub (Bohemica Olomucensia, 2020)
After 1989, the critical discussion in Czech literature went through several important stages regarding the relation between a work of art and social events. Based on this discussion, the presented paper examines the relations between the literary work and its critical reflection and tries to define the "type of social speech production". The starting point for this search is the reasoning by Pierre Macherey, who argues that a literary work is always related to history in some way. The following section of the paper provides the interpretations of the novels by David Zabransky and Vaclav Kahuda.
Keywords: historical novel; social novel; literary criticism; historiographic metafiction